The use of auditory and visual context in speech perception by listeners with normal hearing and listeners with cochlear implants - Winn, Matthew; Rhone, Ariane; Chatterjee, Monita; Idsardi, William (Frontiers in Psychology, 2013)
There is a wide range of acoustic and visual variability across different talkers and different speaking contexts. Listeners with normal hearing accommodate that variability in ways that facilitate efficient perception, but it is not known whether listeners with cochlear implants can do the same. In this study, listeners with normal hearing (NH) and listeners with cochlear implants (CIs) were tested for accommodation to auditory and visual phonetic contexts created by gender-driven speech differences as well as vowel coarticulation and lip rounding in both consonants and vowels. Accommodation was measured as the shifting of perceptual boundaries between /s/ and /ʃ/ sounds in various contexts, as modeled by mixed-effects logistic regression. Owing to the spectral contrasts thought to underlie these context effects, CI listeners were predicted to perform poorly, but showed considerable success. Listeners with cochlear implants not only showed sensitivity to auditory cues to gender, they were also able to use visual cues to gender (i.e. faces) as a supplement or proxy for information in the acoustic domain, in a pattern that was not observed for listeners with normal hearing. Spectrally-degraded stimuli heard by listeners with normal hearing generally did not elicit strong context effects, underscoring the limitations of noise vocoders and/or the importance of experience with electric hearing. Visual cues for consonant lip rounding and vowel lip rounding were perceived in a manner consistent with coarticulation and were generally used more heavily by listeners with CIs. Results suggest that listeners with cochlear implants are able to accommodate various sources of acoustic variability either by attending to appropriate acoustic cues or by inferring them via the visual signal.